1308 Investigating the Use of a Novel Pre-Hospital Triage Tool for Acute Abdominal Surgical Emergencies – A Two-Phase Single Centre Cohort Study. (12th October 2021) - Misbert, E; Hughes, M; Burke, J; Schofield, C; Young, A
Abstract: Background: Despite the recent improvements in mortality in patients undergoing emergency laparotomy(EL) within the UK, delay to theatre continues to be associated with increased mortality. This study aimed to assess if patients requiring urgent surgical intervention for acute abdominal surgical pathology could be identified in the pre-hospital setting. Method: A two-phase, single-centre, cohort study was performed. Phase 1 retrospectively investigated patients who underwent emergency laparotomy between 01/01/2019-31/12/2019 at Leeds Teaching Hospital Trust (LTHT) through the NELA database. Phase 2 prospectively assessed NEWS2 for all patients presenting to LTHT Surgical Admissions Unit with abdominal pain between 01/01/2020-31/01/2020. Results: Phase 1: 45 patients were coded through NELA and confirmed through operation note review as undergoing EL for gastrointestinal perforation. 66%(n = 30) were assessed by the ambulance service and 80% (n = 24) had a NEWS2 of 3 or greater. Phase 2: 319 patients were assessed in SAU/ED, of which 69 initially treated by the ambulance service. 30% (n = 21) of these patients had an initial NEWS2 of 3 or above. Sensitivity of a NEWS2 score of >/3 in predicting the need for immediate surgical intervention including EL was 95%(95%CI, 74-99) and specificity was 95% (95%CI, 83-99) with a PPV of 86%(95%CI 67-95) and NPV of 98% (95%CI, 87-99). Conclusions: A NEWS2 score of >/3 predicts the need for emergency surgical intervention including laparotomy for gastrointestinal perforation with reasonable sensitivity in this cohort. A pre-hospital triage tool for patients presenting with abdominal pain could utilise NEWS2 as an adjunct to decision-making in an acute abdominal pathway.